Structure an charateristics of community-based rural tourism in Costa Rica - Nel-lo Andreu, Marta (Anales de Geografía de la Universidad Complutense, 2008)
Community-based rural tourism in Costa Rica is an advanced stage of ecotourism, under which tourism development is led by families and local communities, who assume responsibility for protecting and capitalising on their natural and cultural heritage. At the national level, the sector is articulated through two networks, Red Ecoturística COOprena R.L. and Asociación Comunitaria de Turismo Rural , who conduct support and promotion programmes aimed at member cooperatives and associations. In order to gain insight into how the sector operates, this article identifies and breaks down by type the main local community-based rural tourism associations, and, based on an analysis of over 50 cases, offers a profile of the main characteristics of current rural tourism initiatives. All of the above should enable an enhanced understanding of the mechanisms and factors that determine the success or failure of any given project. Le tourisme rural au Costa Rica représente une étape avancée de l’écotourisme, donc il incorpore comme le protagoniste de son développement aux communautés locales, qui deviennent responsables pour protéger et mettre en valeur économique le patrimoine naturel et culturel. Au niveau national le secteur s’articule dans deux réseaux: le réseau COOprena R.L. et l’Association Communautaire du Tourisme Rural, qui développent des programmes d’appui et de la promotion dirigés vers les associations et les coopératives membres. Dans l’objectif d’approfondir dans la connaissance du fonctionnement du secteur, dans cet article ils ont été identifiés et classifiés par des typologies les principales associations locales de tourisme rural communautaire et, à partir d’une analyse de plus de 50 cas, les principales caractéristiques profilent. Tous cela doit permettre de comprendre mieux les mécanismes et facteurs qu’ils permettent ou ils compliquent le succès d’une initiative locale.